2006
DOI: 10.1158/0008-5472.can-05-3377
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Cancers to Immunologic Cytotoxicity and Adoptive Immunotherapy via X-Linked Inhibitor of Apoptosis Protein Expression and Coexisting Defects in Mitochondrial Death Signaling

Abstract: The ability of cancers to evade immune surveillance and resist immunotherapy raises a fundamental question of how tumor cells survive in the presence of a competent immune system. Studies to address this question have primarily focused on mechanisms by which tumor cells avoid recognition by or induce tolerance in the immune system. However, little is known about whether cancer cells also acquire an intrinsic ability to resist killing by immune effectors. We find that cancer cells enhance their ability to withs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 53 publications
(65 reference statements)
0
31
1
Order By: Relevance
“…Indeed, granzyme-B transduces death signals either by cleaving Bid to generate gtBid and activate the mitochondrial pathway or by directly cleaving procaspase-3 such as caspase-8. It has been shown that coexisting defects in mitochondrial death signalling together with expression of XIAP induce resistance to immunological cytotoxicity and adoptive immunotherapy (Ravi et al, 2006). Thus, these properties would confer the ability to escape immune surveillance on metastatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, granzyme-B transduces death signals either by cleaving Bid to generate gtBid and activate the mitochondrial pathway or by directly cleaving procaspase-3 such as caspase-8. It has been shown that coexisting defects in mitochondrial death signalling together with expression of XIAP induce resistance to immunological cytotoxicity and adoptive immunotherapy (Ravi et al, 2006). Thus, these properties would confer the ability to escape immune surveillance on metastatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…To reach the critical level of executioner caspases, the release of additional proapoptotic factors such as second mitochondria-derived activator of caspase (SMAC) from the mitochondria is necessary to displace XIAP (X-linked inhibitor of apoptosis protein) from partially processed caspases, thus completing caspase autoactivation (7,8). Elevated XIAP expression or dysfunctional mitochondrial apoptotic pathways in tumor cells are likely responsible for the inadequate caspase activation observed during failed CTL attacks (9,10). The efficacy of adoptive CTL transfer may therefore be improved by restoring the defective mitochondrial apoptotic pathways in tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, besides activating the NF-KB pathway it is also believed to signal through MAPK, JNK and p38 (Varfolomeev et al, 2005). The NF-KB induction has been correlated with TRAIL resistance in multiple cell lines, supporting the proposal of its activity as TRAIL-regulatory (Ravi et al, 2006, Zwacka et al, 2000.…”
Section: Trail: Other Signaling Pathwaysmentioning
confidence: 86%